Peningkatan Literasi Digital Generasi Z di Era Society 5.0 Melalui Pelatihan Patitech Academy Genz Techno Camp - Fajar Husain A; Ryan Yunus; Ellen Proborini; Danang Hendrawan; Nuri Nuri; Muhammad ‘Atiq; Raka Dian Mahardi; Sigit Prakosa A N (Lembaga Pengembangan Kinerja Dosen, 2024)
Generation Z is a generation born in 1997-2012. This generation grew up and developed in the digital era, so they are very familiar with technology. However, the digital literacy of generation Z still needs to be improved, especially in terms of technical and creative skills. On December 25-30, 2023, Patitech Academy held a Genz Techno Camp training. This training was attended by 15 participants, consisting of 7 college students, 6 high school/vocational school/Islamic high school students, and 2 junior high school students. The purpose of this activity is to improve the digital literacy of generation Z, especially in terms of technical and creative skills. This activity also aims to prevent generation Z from falling into negative things during the holidays. The training materials provided include: IoT (Internet of Things), Design graphics, Web programming, Content creator, Digital marketing. This training uses a participatory learning method. Training participants are invited to actively discuss and practice. This training is also supported by competent teaching staff in their fields. The results of the training showed that participants showed an increase in technical and creative skills. They can understand the basic concepts of IoT, graphic design, web programming, content creators, and digital marketing. Training participants can also apply these skills in creating digital products, such as applications, websites, graphic designs, and digital content. The Genz Techno Camp training activity has succeeded in increasing the digital literacy of generation Z. This activity can be an example for various parties to improve the digital literacy of generation Z in a sustainable manner.